Influence of β-cyclodextrin derivatives on the bioavailability and biodistribution of tetrapyrrole compounds - Yakavets, Ilya V.; Yankovsky, Igor v.; Barysau, Kiryl N.; Jukov, Konstantin A.; Belevtsev, Mikhail V.; Bolotine, Lina N.; Zorin, Vladimir P. (Journal of the Belarusian State University. Ecology, 2018)
Due to their unique properties, drug delivery systems based on cyclodextrins are very popular and promising for the development of new drug formulations. Previously, it has been found that cyclodextrins have a high affinity to the aryl substituted tetrapyrrolic compounds which in turn are effective sensitizers for photodynamic therapy. Of special interest for this study is the investigation of β-cyclodextrins (β-CDs) effect on bioavailability and biodistribution of tetrapyrrolic photosensitizer temoporfin (mTHPC) in various biological systems. It was showed that association of mTHPC with the β-CDs completely abolishes its aggregation after introduction into blood serum. Kinetic and equilibrium distribution of mTHPC between β-CDs and serum were studied by means of special fluorescent technique. β-CDs increase diffusion movement of mTHPC molecules between biological structures such as serum proteins. It was demonstrated that the β-CDs have a concentration-dependent effect on the process of mTHPC distribution in blood serum and accumulation in blood cells. The results obtained suggest a significant effect of β-CD molecules on the penetration and distribution of mTHPC in tumor tissue, as well as indicate the possibility of using β-CD to reduce the risk of photoallergic reactions during photodynamic therapy with mTHPC.
Keywords: temoporfin; photosensitizer; inclusion complexes; cyclodextrins; biodistribution